The Role of Esops in Takeover Contests. - Chaplinsky, Susan; Niehaus, Greg (Journal of Finance, 1994)
This article examines both the shareholder wealth effects of employee stock ownership plans (ESOPs) announced by firms subject to takeover pressure and the takeover incidence of targets with and without ESOPs. Although we do not find that defensive ESOPs significantly reduce shareholder wealth on average, we identify two factors - the change in managerial and employee ownership due to the ESOP and the simultaneous announcement of other defensive tactics - that are associated with negative stock price reactions. We find that ESOPs are strong deterrents to takeover. ESOP targets that are acquired earn higher returns than targets without ESOPs, but the difference is not statistically significant.